Cash transfers, polygamy, and intimate partner violence: Experimental evidence from Mali - Heath, Rachel; Hidrobo, Melissa; Roy, Shalini (International Food Policy Research Institute, 2018)
Cash transfer programs primarily targeting women in Latin America and East Africa have been shown to reduce intimate partner violence (IPV), but knowledge gaps remain on how impacts differ by program features and context. Using a randomized control trial, we investigate the IPV impacts of Mali’s national cash transfer program (Jigisémèjiri), which primarily targets men in a West African context where nearly 40 percent of households are polygamous. The program causes significant decreases in IPV in polygamous households – where physical violence decreases by 7 percentage points, emotional violence decreases by 12 percentage points, and controlling behaviors decrease by 16 percentage points -- but has limited effects in nonpolygamous households. Evidence on mechanisms suggests that the program led to significant decreases in men’s stress and anxiety among polygamous households, and larger reductions in disputes in polygamous households compared to non-polygamous households.